Ozone in Nature and Practice 2018
DOI: 10.5772/intechopen.76843
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Dosage is the Key Factor of Its Effect in Biological Systems

Abstract: The applications of ozone are not only restricted to environmental remediation or industrial areas. This gas has been applied in medicine to treat several diseases, where positive effects have been confirmed by many clinical studies. According to the European Medical Society of Ozone and the National Center of Scientific Investigation in Cuba, it has not been possible to validate ozone's effectiveness by traditional analytical methods. Thus, this investigation proposed evaluating the effect that ozone has on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…This indicated that the peroxides formed during that process are responsible for the biocidal effect and that a longer ozonation times involves the presence of higher amounts of compounds with biocidal activ-ity. This result is consistent with the criterion that the mixture of peroxy compounds formed by ozonation constitutes the active pharmaceutical ingredient in these oils and is in good agreement with previous results (Poznyak et al, 2018). The MIC values obtained for each microorganism are related to their morphological and physiological characteristics.…”
Section: Determination Of the Antimicrobial Activity Of Oxidized Sunf...supporting
confidence: 92%
“…This indicated that the peroxides formed during that process are responsible for the biocidal effect and that a longer ozonation times involves the presence of higher amounts of compounds with biocidal activ-ity. This result is consistent with the criterion that the mixture of peroxy compounds formed by ozonation constitutes the active pharmaceutical ingredient in these oils and is in good agreement with previous results (Poznyak et al, 2018). The MIC values obtained for each microorganism are related to their morphological and physiological characteristics.…”
Section: Determination Of the Antimicrobial Activity Of Oxidized Sunf...supporting
confidence: 92%
“…Interestingly, ozone therapy has been documented to reduce oxidative stress and inflammation, which are the established hallmarks of chronic wounds and, thus, provides a curative potential against chronic wounds [ 7 ]. It has been reported that ozone at 5–60 mg/L concentration is recommended for medical implementations where it exerts various therapeutic effects without having any deleterious ramifications [ 8 , 9 ]. In low doses, ozone stimulates cell protective activity [ 10 ], ameliorates tissue oxygenation, and activates the nuclear factor erythroid 2-related factor 2 (Nrf-2) pathway that regulates the expression of superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and other endogenous antioxidants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standardized guidelines and best practices are continuously evolving to establish safe and effective ozone therapy protocols, thereby supporting healthcare practitioners in harnessing the full potential of this innovative treatment modality. By adhering to meticulous concentration control, medical and dental professionals can harness the therapeutic benefits of ozone while safeguarding patient well-being throughout the treatment process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%